Assessing Transitions to Sustainable Agricultural and Food Systems: A Tool for Agroecology Performance Evaluation (TAPE) - Mottet, Anne; Bicksler, Abram; Lucantoni, Dario; De Rosa, Fabrizia; Scherf, Beate; Scopel, Eric; López-Ridaura, Santiago; Gemmil-Herren, Barbara; Bezner Kerr, Rachel; Sourisseau, Jean-Michel; Petersen, Paulo; Chotte, Jean-Luc; et al. (Frontiers in Sustainable Food Systems, 2020)
There is increasing interest in agroecology as a way to move towards more sustainable agriculture and food systems. However, the evidence of agroecology’s contribution to sustainability remains fragmented because of heterogeneous methods and data, differing scales and timeframes, and knowledge gaps. Facing these challenges, 70 representatives of agroecology-related organisations worldwide participated in the development of the Tool for Agroecology Performance Evaluation (TAPE), to produce and consolidate evidence on the multidimensional performances of agroecological systems. TAPE is composed of: Step 0, the preliminary step that includes a description of the main socio-economic and demographic characteristics of the agricultural and food systems and an analysis of the enabling environment in terms of relevant policy, market, technology, socio-cultural and/or historical drivers; Step 1, the Characterization of Agroecological Transitions (CAET), based on the 10 Elements of Agroecology adopted by FAO and its member countries, using descriptive scales to establish scores and assessing the degree of transition, with information from the farm/household and community/territory scale; Step 2, the Core Criteria of Performance listing the key dimensions considered relevant to address the Sustainable Development Goals (SDGs): Environment & climate change; Health & nutrition; Society & culture; Economy and Governance. Finally Step 3, a participatory validation of the results obtained from the previous steps with the producers and relevant stakeholders. TAPE can be used (i) to assess the extent of agroecological transition among agricultural producers in a community/territory, (ii) to monitor and evaluate projects by characterizing the initial and subsequent steps in an agroecological transition, and/or (iii) to evaluate widely diverse agricultural systems against agroecological elements and how they contribute to the achievement of the SDGs. Its application can support the transition of all forms of agricultural systems towards more sustainable practices and the formulation of adequate policies to enable this transformation. Preliminary results from pilot applications show that TAPE can perform in a variety of geographic regions and agroecosystems and that it allows assessment of performances of various criteria that move beyond classic indicators to begin to build a global evidence base for agroecology and support transformation to sustainable agricultural production and food systems.